Angle Surgery in Pediatric Glaucoma Following Cataract Surgery - Jamerson, Emery C. (Vision (Basel), 2021)
Glaucoma is a common and sight-threatening complication of pediatric cataract surgery Reported incidence varies due to variability in study designs and length of follow-up. Consistent and replicable risk factors for developing glaucoma following cataract surgery (GFCS) are early age at the time of surgery, microcornea, and additional surgical interventions. The exact mechanism for GFCS has yet to be completely elucidated. While medical therapy is the first line for treatment of GFCS, many eyes require surgical intervention, with various surgical modalities each posing a unique host of risks and benefits. Angle surgical techniques include goniotomy and trabeculotomy, with trabeculotomy demonstrating increased success over goniotomy as an initial procedure in pediatric eyes with GFCS given the success demonstrated throughout the literature in reducing IOP and number of IOP-lowering medications required post-operatively. The advent of microcatheter facilitated circumferential trabeculotomies lead to increased success compared to traditional <180° rigid probe trabeculotomy in GFCS. The advent of two-site rigid-probe trabeculotomy indicated that similar results could be attained without the use of the more expensive microcatheter system. Further studies of larger scale, with increased follow-up, and utilizing randomization would be beneficial in determining optimum surgical management of pediatric GFCS.